Indigenous nations and the development of the US economy: Land, resources, and dispossession - Ann M. Carlos; Donna Feir; Angela Redish (Queen's University Centre for Economic History (QUCEH), 2021)
Abundant land and strong property rights are conventionally viewed as key factors underpinning US economic development success. This view relies on the "Pristine Myth" of an empty undeveloped land. But the abundant land of North America was already made productive and was the recognized territory of sovereign Indigenous Nations. We demonstrate that the development of strong property rights for European/American settlers was mirrored by the attenuation and increasing disregard of Indigenous property rights and that the dearth of discussion of the dispossession of Indigenous nations results in a misunderstanding of some of the core themes of US economic history.
Keywords: N40; N41; N50; N51; 330; indigenous peoples; development of the American economy; Institutions